Bird strike assessment for a composite wing flap. Issue 2 (4th March 2018) - Orlando, S.; Marulo, F.; Guida, M.; Timbrato, F.
ABSTRACT: The paper presents the design, analysis and test of the CFRP flap to demonstrate its compliance with the regulation and safety standards toward the bird strike requirement. The purpose of this work is to define a methodology based on the finite element analysis to predict the damage for high-velocity impact of a full-scale aircraft component using the SPH bird impact model, 4 lb, at a velocity of 194 kts (100 m/s). In order to validate the numerical models, materials were initially characterised through an extensive campaign of tests aimed to identify their static and dynamic properties. The bird strike simulation was carried out, first on a rigid plate to correlate the experimental test performed by Barber, and then the results were extended for a selected composite panel to investigate the particle's distance for the SPH approach and pressure path distributed on the target, and finally these validated results were applied on the flap structure. The numerical simulations have been used from the initial designing phase as well as for the certification according to the aeronautical requirements, to be able to design a flap structure and the relative fixture reproducing the real test condition. Finally, the flap has been manufactured, tested, certified and installed on the large commercial aircraft.